Cambios electromiográficos después de cirugía ortognática: reporte de cuatro casos - Duque-S., Francisco L.; Jaramillo-V., Pedro M.; Farbiarz-F., Jorge; Álvarez-M., Diego L.; Peláez-V., Alejandro; Otálvaro-C., Gabriel J. (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The purpose oJ the study was evaluated the electromyographic, cephalometric and contact points changes in four patients treated by orthodontics and orthognatic surgery. BeJore and afler surge/y the patient S electric activity was analyzed by masseter, temporalis and suprahyoid electromyography, cephalometric study and contact points. Statistic analysis and error test were assessed. The results showed and electrical activity change afler the orthognatic surgery. These changes could no be placed together beca use oJ the individual variability. The cephalometric changes were significantly changed and the contact points increased. The electromyographic changes could be explained because of the muscle force vector; the muscle insertions and an increase in the contact points. The change might take to a better stability and higher electromyography activity.